2014
DOI: 10.5455/jva.20141221083415
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Foot and Mouth Disease Virus circulating in Bangladesh by Reverse Transcription Polymerase Chain Reaction

Abstract: Foot and Mouth Disease (FMD) is one of the highly contagious diseases of domestic and wild animals of many countries of the world including Bangladesh. The present study was undertaken to detect currently circulating FMD virus (FMDV) in Bangladesh using BHK-21 cell line, and the FMDV were typed using RT-PCR. The viruses induced characteristics cytopathic effects in BHK-21 cell lines, for examples, rounding, swelling, breaking down of intercellular bridge and cell death. Out of 151 clinical samples collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
6
13
0
Order By: Relevance
“…4). Similar observation was also reported by Loth et al (2011) and Hossen et al (2014). However, effect of this mutation on the virulence of FMD virus was not evaluated.…”
Section: Sequence and Phylogenetic Analysissupporting
confidence: 71%
“…4). Similar observation was also reported by Loth et al (2011) and Hossen et al (2014). However, effect of this mutation on the virulence of FMD virus was not evaluated.…”
Section: Sequence and Phylogenetic Analysissupporting
confidence: 71%
“…Mixed infection having Type A and Asia-1 FMDV was also detected (Hossen et al, 2014). Epidemiological investigation of this virus in cattle population indicated that four different types (A, O, C and Asia-1) of FMDV were prevalent in Bangladesh during 1960 to 1990 (Chowdhury et al, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Detection of FMDV PCR has been described , 2015; Hossen et al, 2014;Loth et al, 2011;Saeed et al, 2011). We have performed PCR after synthesis of cDNA from the extracted RNA of the FMD virus and found positive bands at 866bp after electrophoresis in 2% agarose gel which was specific for FMDV serotype "A" (Figure 2 Present study proved that FMDV serotype "A" is present in the Pabna district of Bangladesh.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…144.0 /animal), draught energy wastage average 12.48 kilo watt hr/animal, and land left uncultivated average .72/ animal (Rahman et al, 1985). A lot of epidemiological and molecular research works have been conducted on FMD virus but in clinical aspects has few studied in Bangladesh (Islam et al, 2000;Howlader et al, 2004;Sarker et al, 2011;Hossen et al, 2014;Rahman et al, 2015) and in the world (Edwards, 2004;Durand et al, 2008;Fernandez et al, 2008;Ryan et al, 2008;Huang et al, 2011). There is no published data so far on prevalence of FMD in Gazipur district of Bangladesh although this region has huge number of livestock population.…”
Section: Introductionmentioning
confidence: 99%